2005
DOI: 10.1002/ijc.21477
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional analysis of oncogenic HPV viral load and cervical intraepithelial neoplasia

Abstract: In human papillomavirus (HPV)-associated carcinogenesis, HPV infection characteristics such as viral load may play an important role in lesion development. The purpose of this study was to determine the association between quantitative assessment of oncogenic HPV viral load, and abnormal cytology among women residing along the United States-Mexico border. A cross-sectional study of 2,319 women was conducted between 1997 and 1998. Viral load of oncogenic HPV types (16,18,31,39, 45, 51, 52, and 58) was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
6
10

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 40 publications
5
49
6
10
Order By: Relevance
“…However, a controversial observation has been reported, showing inconsistent results with significantly less HPV 16 viral load in high-grade squamous intraepithelial lesions than low-grade squamous intraepithelial lesions. 49 Our results in formalin-fixed paraffin-embedded material showed that the HPV 16 viral load was proportionally associated with the grade of cervical lesions, with higher viral loads in higher grades of the lesions, but lack of statistical significance.…”
Section: Discussionmentioning
confidence: 58%
“…However, a controversial observation has been reported, showing inconsistent results with significantly less HPV 16 viral load in high-grade squamous intraepithelial lesions than low-grade squamous intraepithelial lesions. 49 Our results in formalin-fixed paraffin-embedded material showed that the HPV 16 viral load was proportionally associated with the grade of cervical lesions, with higher viral loads in higher grades of the lesions, but lack of statistical significance.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, our study did not provide information on HPV viral load, and therefore, it cannot evaluate whether any of the considered characteristics affected viral replication, thereby increasing viral load. OC use and parity were not reported to be associated with viral load among HPV-positive women (48). Finally, our questionnaire did not allow the distinction between OC with combined estrogen and progestagen, or progestagen only.…”
Section: Discussionmentioning
confidence: 90%
“…Deve ser tomado cuidado com a possibilidade de quadros de latência levarem a falsos positivos e, portanto, sobrediagnóstico. A possibilidade de diferença entre a carga viral e o diagnóstico da lesão tem sido estabelecida em vários estudos 6,7,8,10,12,13,15,18,22 , embora contestados por outros 23,24 . De fato, o "cutoff" que permite uma melhor performance do teste no diagnóstico de HSIL tem sido bastante variável.…”
Section: Discussionunclassified
“…Assim, hoje se sabe que o tipo 16 é o mais prevalente em todo o mundo 1 , independentemente da gravidade da lesão escamosa, e, de maneira geral, os HPV identificados como de alto risco estão presentes em mulheres imunocompetentes em cerca de 20% dos quadros histológicos negativos, em 70% dosUNIOR UNIOR*, P *, P *, P *, P *, PAULO AULO AULO AULO AULO C C C C CÉSAR ÉSAR ÉSAR ÉSAR ÉSAR G G G G GIRALDO IRALDO Vários pesquisadores defendem a idéia de que a alta carga viral de HPV de alto risco teria uma importante relação com lesões intraepiteliais escamosas e sua maior gravidade 6,7,8,10,12,15,18,22 . Outros pesquisadores enfatizam a importância da persistência da alta carga viral por longo tempo, e não simplesmente uma medida isolada, assim como só teria valor a alta carga viral do HPV tipo 16, sem considerar os demais tipos 2,3,9,13,14,16,17 .…”
Section: Introductionunclassified
See 1 more Smart Citation